Author Correction: Multiple Approaches Detect the Presence of Fungi in Human Breastmilk Samples from Healthy Mothers. Issue 1 (December 2018) - Boix-Amorós, Alba; Martinez-Costa, Cecilia; Querol, Amparo; Collado, Maria; Mira, Alex
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.